Analisis Faktor-Faktor yang Berhubungan dengan Tingginya Rujukan Kasus Non Spesialistik Pasien Jaminan Kesehatan Nasional pada Puskesmas di Kabupaten Sukabumi Tahun 2015 - Alawi, Masykur; Junadi, Purnawan; Latifah, Siti Nur (UI Scholars Hub, 2017)
Public Health Center is the frontline in the basic health services that include non-specialist cases to be solved in this primary health care level. However, a report from BPJS Kesehatan in 2015 showed that there were 11.487 referral of non-specialist cases in Primary Health Cares (PHCs) in Sukabumi. This study was to determine factors associated with high referral rate of National Health Insurance’s members with non-specialist cases by PHCs in Sukabumi in 2015. The study employed cross-sectional design in 58 PHCs along with a general practitioner in each centers using a whole sampling. The result showed that there were correlation between characteristics of the region (P=0,000); adequacy of drug (P=0,040); adequacy of medical devices (P=0,024); and distance from the PHCs to the referral health care facilities (P=0,003) with non-specialist cases referral rate. It is recommended for the PHCs to meet the needs of drugs, medical devices according to the standard, monitor and evaluate the non-specialist referral cases, both from health centers and the Social Security Agency for Health of Sukabumi.